Assessment of the Severity and the Remission Criteria in Eosinophilic Esophagitis - Ksenia Maslenkina; Liudmila Mikhaleva; Alexander Mikhalev; Valeria Kaibysheva; Dmitri Atiakshin; Eugeny Motilev; Igor Buchwalow; Markus Tiemann (Biomedicines, 2023)
Eosinophilic esophagitis (EoE) is an immune-mediated disease that manifests with dysphagia and is characterized by the predominantly eosinophilic infiltration of the esophageal mucosa. Several instruments have been developed to assess the symptoms of EoE: the Daily Symptom Questionnaire (DSQ), EoE Activity Index (EEsAI), Pediatric EoE Symptom Severity (PEESSv2), etc. The use of the EREFS is a gold standard for endoscopic diagnosis. The EoE histologic scoring system (EoEHSS) was elaborated for the assessment of histological features in EoE. However, the remission criteria are not clearly defined and vary greatly in different studies. Gastroenterologists establish the severity of EoE mainly based on endoscopic findings. At the same time, EoE requires a multidisciplinary approach. The recently developed Index of Severity of Eosinophilic Esophagitis (I-SEE) that is built on symptoms, endoscopic findings, and histological features is promising.